Herbal for increasing immunity and weight of poultry. (March 2019) - Haniarti,; Munir,; Akib, M A; Ambar, A; Rusman, A D P; Abdullah, A
Abstract: The use of natural materials as a drug tends to increase with the issue back to nature and the prolonged crisis caused a decline in the purchasing power of modern medicines are relatively more expensive. Natural medicine is also considered almost no harmful side effects. The research question to be answered in the third year of research: (1) What medicinal benefits to the immune system and increase the weight of poultry (2) The form of herbal preparations which one is more effective administration, such that to bjective of this study is to: (1) Improveendurance and body weight of poultry (2) Getting the dosage of herbal medicine more effective administration. This study will be conducted in the town of Pare-pare for 10 months in the third year (April to December 2018). Research compiled by factorial design was completely randomized design (CRD), as many as 50 chickens aged 14 days were divided into 3 treatment. Parameters measured were anincrease in endurance and chicken body weight, while the level of drug dosage forms (herbal medicine) herbal so consist sof three levels, namely Extractum (control), pulvis, and kapsulae. The results of the study state that livestock can be an alternative herbal medicine as a drug because it can increase the resistance of chickens so that the mortality rate decreases. Of the three doses given, capsule dosing is more effective.